Abraham. Ten, który wbrew nadziei uwierzył nadziei - Pawłowski, Zdzisław (Verbum Vitae, 2006)
In this article entitled ’Abraham: the one w ho against hope, in hope believed’ we have tried to defin a hope in terms of narrative transformation of Abraham’s identity. Abraham as a member of a genealogical tree of Terah lived in a history and a world of his father, unable to live his own independent life (Gen 11,27-32). Only the word of God’s promise (Gen 12,1-3) bas been powerful enough to turn him into a new person, opened towards future. In this process hope bas been playing an indispensable role. Shaped by the promise it transgresses every historical circumstances towards eschatological goal.